The Psychology of the extreme - Kruglanski, Arie W. (The psychology of everything, 2025)
"What does extremism mean? How does it show up in our daily lives? What drives people to extreme behaviours, and how can we learn to live and thrive in the age of overdrive? The Psychology of the Extreme provides an accessible introduction to extremism as a force that can affect all aspects of culture and people's choices in everyday settings. It explores the underlying psychology behind what makes people act in extreme ways, whether this is in destructive ways (such as gambling, terrorism and political violence) or in constructive ways (such as successful creators and scientists). The book features an array of case studies that show how extremism can be both prosocial and antisocial and includes interventions to reduce extremism or redirect them towards more positive and constructive tendencies. Offering a new understanding of the individual psychology of extremism, the book will appeal to all those interested in how extremism plays out in people's and cultures day-to-day lives"--